Incidence and Prevalence of Inflammatory Bowel Disease in Osijek-Baranja County, Croatia, 2000-2014 - Marinko Žulj; Marija Raguž; Ana Petrović; Kristina Kralik; Brankica Juranić; Štefica Mikšić; Marko Boban; Robert Smolić (Acta Clinica Croatica)
The etiology of inflammatory bowel disease (IBD) is unknown. Data on the incidence and prevalence in different regions can help identify factors relevant to the occurrence of IBD. From 2000 to 2014, 517 patients were newly diagnosed with IBD, including 329 (63.6%) patients with ulcerative colitis (UC) and 188 (36.4%) patients with Crohn’s disease (CD). The incidence of UC was 71.4/100,000 in the 2000-2010 period and 30.5/100,000 in the 2011-2014 period. The incidence of CD was 37.5/100,000 in the 2000-2010 period and 21/100,000 in the 2011-2014 period. The prevalence of IBD showed an increasing trend during the study period. It increased from 3/100,000 in 2000 to 109.5/100,000 in 2014 for UC, and from 2.5/100000 in 2000 to 63.3 in 2014 for CD. The results from Osijek-Baranja County are consistent with most studies on IBD, except for the distribution by gender and education. There was a statistically significantly higher number of males with CD compared to UC, and patients diagnosed with CD had a significantly higher level of education.